THE EFFECT OF SOAKING SALTS CONCENTRATION TO CANDIED GARLIC (Sativum allium L.) - Titaley, Naning Restiani; Herawati, Maria Marina (Jurnal Ilmu Pangan dan Hasil Pertanian, 2019)
Garlic has a bitter taste, which makes people reluctant to eat one whole garlic clove. The salt soaking technique used to reduce the bitter taste of the garlic, and the garlic processed into wet candied garlic, so it became more edible than not process. The process of candied garlic could preserve the durability level, which allows it to be stored longer at low temperatures. The research materials used were salt and sugar. The purpose of the research was to know the effect of salt concentration on reducing bitterness and the right concentration to reduce the bitter taste of garlic. This research used the RAK method, and DMRT (Duncanâ€™s Multiple Range Test), and the samples of salt were 3%; 3.5%; 4%; 4.5%. The test included chemical tests (water content and total microbes) and organoleptic tests (taste, aroma, and texture). The water content of the product showed the result, which was not significantly different, and the total microbes test showed no microorganism was found or grew on the product. The organoleptic test of taste was obtained on 3.5% salt, with an average of 2.75% (likes), while the aroma and texture did not show a significant difference in the result. The aroma and texture data obtained on 2.90 (likes) and 2.40 (likes) with 3.5% salt.Â Keywords: Candied; Garlic; Salt; Soaking; Sugar.